Transformasi Sumber Daya Lokal Menuju Produk Bernilai Jual di Desa Balongwono Kecamatan Trowulan Kabupaten Mojokerto - Lailatus Sa'adah; Ita Rahmawati; Mufidatul A’yun; Malikha Fitri; Candra Nur Adiputra; Ihsanuddin Aqda (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2026)
Developing local resources into high-value products is an important strategy in improving the economic welfare of rural communities. This study focuses on the transformation of local potential in Balongwono Village, such as the abundant melon harvest that can be processed into melon jam, pickled melon, banana stems into banana stem chips, and spinach into spinach chips. Considering that so far there are many local resources that have not been utilized properly to become products with sales value, in addition, the community still markets their products traditionally. The methods used are lectures through seminars and mentoring of MSMEs and PKK mothers to improve understanding and skills in marketing local products digitally. as well as mentoring the creation of social media accounts. In addition, an evaluation using a questionnaire was conducted regarding the understanding of the transformation of local products into products with sales value. The method used was a lecture combined with evaluation through pretest and posttest to assess the program's effectiveness. Results show a significant increase in the average score of participants from 72.33% before the seminar to 93% after the seminar, indicating the program's success in enhancing the capacity of local entrepreneurs. These findings suggest that community service activities serve as a strategic solution to strengthen the competitiveness of local products and community economic independence.